Natural flow regime of the Ayuquila-Armeria River in western Mexico. - Martinez Rivera, Luis Manuel; Meza-Rodríguez, Demetrio; Mercado-Silva, Norman; García de Jalón-Lastra, Diego; González del Tánago-Del Rio, Marta; Marchámalo-Sacristan, Miguel; De la Mora Orozco, Celia (REVISTA TERRA LATINOAMERICANA, 2017)
Surface flow at the basin level is now a key process in hydrological studies of any kind. This research explores the reconstruction of the natural flow regime of the Ayuquila-Armería River basin for the period 1963‑1991. The importance of reconstructing the flows in this study is that the designed method can be extrapolated to other basins in Mexico and Latin America where there are no specific hydrometric data. The field of study of interest is focused on the technique of reconstruction of natural flow based on precipitation and temperatures in situations where there is no specific hydrological information, using the deterministic model “precipitation-runoff”. This model requires few parameters for its implementation. Using the Geographic Information Systems (GIS), climatic and physical processes in the space and time domain are defined. From calibrated flows in the same geographical area, it is possible to extrapolate the prediction model to the entire basin. The result was a 29-year database of natural flow regime, which showed a flow rate of approximately 71.5 (m3 s-1) and an annual volume of 2254 (hm3 year‑1); seasonal patterns and fluctuations were observed throughout the year. The use of this methodology will support the new standard NMX-AA-159-SCFI-2012, for which the scientific principle for determination of ecological flow is a paradigm of the natural hydrological regime.